Coupling Root Diameter With Rooting Depth to Reveal the Heterogeneous Assembly of Root-Associated Bacterial Communities in Soybean - Luo, Wen; Zai, Xiaoyu; Sun, Jieyu; Li, Da; Li, Yuanli; Li, Guoqiang; Wei, Gehong; Chen, Weimin (Frontiers in Microbiology, 2021)
Root diameter and rooting depth lead to morphological and architectural heterogeneity of plant roots; however, little is known about their effects on root-associated microbial communities. Bacterial community assembly was explored across 156 samples from three rhizocompartments (the rhizosphere, rhizoplane and endosphere) for different diameters (0.0–0.5 mm, 0.5–1.0 mm, 1.0–2.0 mm and >2.0 mm) and depths (0–5 cm, 5–10 cm, 10–15 cm and 15–20 cm) of soybean (Glycine max (L.) Merrill) root systems. The microbial communities of all samples were analyzed using amplicon sequencing of bacterial 16S rRNA genes. The results showed that root diameter significantly affected the rhizosphere and endosphere bacterial communities, while rooting depth significantly influenced the rhizosphere and rhizoplane bacterial communities. The bacterial alpha diversity decreased with increasing root diameter in all three rhizocompartments, and the diversity increased with increasing rooting depth only in the rhizoplane. Clearly, the hierarchical enrichment process of the bacterial community showed a change from the rhizosphere to the rhizoplane to the endosphere, and the bacterial enrichment was higher in thinner or deeper roots (except for the roots at a depth of 15–20 cm). Network analysis indicated that thinner or deeper roots led to higher bacterial network complexity. The core and keystone taxa associated with the specific root diameter class and rooting depth class harbored specific adaptation or selection strategies. Root diameter and rooting depth together affected the root-associated bacterial assembly and network complexity in the root system. Linking root traits to microbiota may enhance our understanding of plant root-microbe interactions and their role in developing environmentally resilient root ecosystems.